2019
DOI: 10.1186/s13046-019-1129-8
|View full text |Cite|
|
Sign up to set email alerts
|

Pancreatic cancer-initiating cell exosome message transfer into noncancer-initiating cells: the importance of CD44v6 in reprogramming

Abstract: BackgroundCancer-initiating cell (CIC) exosomes (CIC-TEX) are suggested reprogramming Non-CIC. Mode of message transfer and engagement of CIC-markers being disputed, we elaborated the impact of CD44v6 and Tspan8 on the response of Non-CIC.MethodsNon-metastasizing CD44v6- and Tspan8-knockdown (kd) pancreatic cancer cells served as Non-CIC. CIC-TEX coculture-induced changes were evaluated by deep-sequencing and functional assays. Tumor progression was surveyed during in vivo CIC-TEX treatment.ResultsDeep-sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 83 publications
2
51
0
Order By: Relevance
“…The reverse, a lower signal strength in both ASML-Tspan8kd-TEX and AS-TEX accounted only for 10 miRNA ( Figure S2E,F). Though confirming a slight impact of Tspan8 on miRNA recovery in TEX, we recently elaborated that we are dealing with an indirect effect due to Tspan8 associating with proteins that are directly engaged in miRNA recruitment into ILV [54].…”
Section: The Mrna and Mirna Profile Of Endothelial Cells Fibroblastsmentioning
confidence: 65%
See 4 more Smart Citations
“…The reverse, a lower signal strength in both ASML-Tspan8kd-TEX and AS-TEX accounted only for 10 miRNA ( Figure S2E,F). Though confirming a slight impact of Tspan8 on miRNA recovery in TEX, we recently elaborated that we are dealing with an indirect effect due to Tspan8 associating with proteins that are directly engaged in miRNA recruitment into ILV [54].…”
Section: The Mrna and Mirna Profile Of Endothelial Cells Fibroblastsmentioning
confidence: 65%
“…TEX received much attention as transferring tumor-growth and -progression promoting activities into non-cancer-initiating cells (Non-CIC) [88] as well as host cells promoting (lymph)angiogenesis [7,89], premetastatic niche establishment [8][9][10], and deviation of hematopoietic cells towards immunosuppression [90]. We recently elaborated the mode whereby CIC-TEX affect Non-CIC, which revealed that an impact of TEX-Tspan8 predominantly relies on the engagement of Tspan8 complexes in TEX biogenesis [5,30,54,57,91] including the transfer of Tspan8-associated CIC-markers into TEX and, most importantly, on Tspan8 facilitating TEX binding and uptake by target cells via ligands for Tspan8-associated molecules [5,27,38,52,55,68]. Uptaken TEX stimulating non-CIC inherent programs [5,30,54] and Tspan8 being particularly engaged in TEX binding and uptake, we asked whether non-transformed cells respond alike oncogene-transformed cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations